(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Pneumonia remains the most common and severe disease of the respiratory system in children. Understanding the immune status and the pathogenetic role of cytokines will help to better understand the mechanisms of the development of the disease in pneumonia, to develop effective strategies for the diagnosis and treatment of the disease in frequently ill children. The aim of the scientific research is to study the status of cytokines in mycoplasma pneumonia in frequently ill children. Research materials and methods: 50 patients with pneumonia divided into 2 groups were examined to establish correlation with cytokine profile indicators: Group I - 25 frequently sick children with a typical etiology of pneumonia, II group - 25 children with mycoplasma pneumonia. The study showed that cytokines are one of the main mediators of pathogenesis and regulate the accumulation and activation of immune cells and inflammatory processes in the airways.